Toxicological Assessment of Ethanolic Leaves Extract of Kalanchoe pinnata in Rats - V. Saravanan; S.S. Murugan; K.R. Navaneetha Krishnan; N. Mohana; K. Sakthivel; T. N. Sathya (Institute of Medico-legal Publications Pvt Ltd, 2021)
Kalanchoe pinnata is a perennial plant that is widely used in the folklore treatment of kidney and gallstones and urinary insufficiency. The present study aims to evaluate the potential toxicity of the leaf extractof this plant upon acute and sub-acute (28 day) exposure in Wistar rats when administered orally. In Acuteoral toxicity(n=3) Female Wistar rats were treated with a single dose of 2000mg/kg b.wt and observed for14 days and Sub-acute toxicity(n=6) Male and Female Wistar rats were treated with the dose of 500 and1000mg/kg b.wt of leaf extract for 28 days consecutively. No mortality, morbidity or adverse clinical signsof toxicity were observed during the experimental period. No significant changes in the body weight wasobserved. Gross necropsy did not indicate any treatment-related pathological changes in any of the animalsin the acute and sub-acute toxicity studies. Histopathology of the Liver, Heart and Kidney did not show anyremarkable lesions that could be related to the administration of the leaf extract. Ethanolic leaf extract ofKalanchoe pinnata is relatively safe with an LD50 value greater than 2000 mg/kg. From the sub-acute study,the no-observed adverse effects level (NOAEL) of the extract can be derived as 1000 mg/kg b.wt in maleand female Wistar rats.